When a good company transgresses: A study of the influences of CSR, moral decoupling, and ethnocentrism. Issue 1 (2nd January 2017) - Chang, Dae Ryun; Jang, Joonsuk; Lee, Eric Y.; Lee, Hosun; Chang, Boinn
Abstract: Transgressions can result in negative consequences, especially when committed by global companies. Some of the biggest multinational companies in the world take extra steps to be socially responsible and to have positive reputations in domestic and foreign markets. Despite the extra steps that may be taken, it is a common occurrence for some of these companies to commit transgressions. The knowledge of the effect of corporate social responsibility (CSR) history and the country of origin of transgressing companies is scarce in studies that examine the consumers' reasoning process to forgive or not to forgive the transgression. While the moral reasoning process to forgive transgressions has been examined in instances with public figures, studies are lacking in the instance of companies. This study will bridge these gaps by examining the effects of CSR history and consumer ethnocentrism on the evaluation of companies before and after transgressions. This study will also examine the effects of company evaluations before and after transgressions in the reasoning process of consumers. The authors conclude the study by discussing implications for marketing managers and the potential for further research.